Relevance of Workplace Behavior on the Achievement of Organizational Goals - Acuña Benites, Robin Alberto (2023)
One of the most commonly discussed topics in company meetings is the performance of workers in individual and team tasks, and the attitudes and decisions adopted by individuals which are often due to personal reasons. For this reason, it is important for organizations to consider evaluating workers' behavior in order to reach their organizational goals. Some organizations have job candidates sit a psychological evaluation to find out about their character and behavior because they are aware that, nowadays, it is not enough to meet experience and academic requirements. In fact, when workers show appropriate behavior in their work plus excellent teamwork skills, the organization will follow the correct path and achieve its expected goals. If the workers' behavior is understood, it is possible to propose mechanisms to modify it or direct it toward the benefit of both the organization and the individuals themselves.